Darkroom prone provocative testing in primary angle closure suspects and those with open angles. Issue 12 (28th February 2019) - Friedman, David S; Chang, Dolly Shuo-Teh; Jiang, Yuzhen; Huang, Shengsong; Kong, Xiangbin; Munoz, Beatriz; Aung, Tin; Foster, Paul J; He, Mingguang
Abstract : Purpose: To describe the results of darkroom prone provocative testing (DRPPT) in primary angle closure suspects (PACS) and to compare the findings to controls with open angles. Methods: 889 subjects with PACS in the Zhongshan Angle Closure Prevention Trial (a randomised controlled trial to compare prophylactic laser iridotomy to no treatment in PACS) and 89 with open angles in the 5-year follow-up of Liwan Eye Study were placed in a darkroom face down for 15 min. Intraocular pressure (IOP) was measured immediately before and after DRPPT. Results: PACS participants were of similar age than controls (59.3 vs 60.5), more often female (82.9% vs 58.4%) and had lower IOP (14.3 vs 15.2 mm Hg). The average IOP increases after DRPPT was 4.3±3 mm Hg in PACS and 5.2±2.8 in controls (p<0.05). 20.5% of controls and 13.9 % of those with PACS developed an IOP spike ≥8 mm Hg after DRPPT (p<0.05). Among PACS, 15.8 % of those with all four quadrants closed had an IOP elevation of ≥ 8 mm Hg as opposed to 10.0%–12.4 % with two or three closed quadrants (p<0.05). DRPPT failed to predict who would reach a clinical trial endpoint over 6-year follow-up of those with PACS. Conclusions: A modified DRPPT failed to separate PACS from those with open angle. Although the test resulted in greater IOP elevation among those PACS participants with all four quadrants closed than in those with two or three closed quadrants, it did not offer any insight into the risk of developing acute or chronic angle closure disease over 6-year follow-up.